ショウワキチ ニ オケル カイヒョウカ ノ クロロフィル aリョウ ト カンキョウ ジョウケン ノ キセツ ヘンカ - 星合, 孝男; ホシアイ, タカオ; HOSHIAI, Takao (国立極地研究所, 1969)
P(論文) From March 1967 to January 1968, ecological studies on the seasonal variation of the chlorophyll-a content and some of hydrographic factors, viz chlonmty, dissolved oxygen and pH under sea ice, were carried out at Syowa Station The results obtained are as follows 1 Judging from high concentration of chlorophyll-a, it seemed that the dense population of phytoplankton was formed under sea ice during the Antarctic summer season The chlorophyll-a concentration increased and decreased in accord with increase and decrease of the solar radiation 2 First, the chlorophyll-a concentration increased and reached a peak in the surface layer of the sea water (0 m in Figures) Increase of the chlorophyll-a concentration in deeper layers occurred later 3 In the surface layer two peaks of the chlorophyll-a concentration were recognized in both spring and autumn, but one peak in each of deeper layers in summer 4 Influence of the thaw was remarkable in summer, especially in the surface water Consequently, a thin layer of water of low salinity was formed beneath the sea ice and it seemed to remain till autumn Water of high salinity occupied the layers deeper than 4 meters, and was hardly influenced by the thaw 5 The seasonal variation and the vertical distribution of dissolved oxygen were correlated with the temporal and spatial distributions of the chlorophyll-a concentration 6 The variation of pH was also related with chlorophyll-a, so that the pH value varied with dissolved oxygen In the surface water, however, the pH value was influenced not only by phytoplankton but also by thaw water 7. At Syowa Station, two stations were chosen for this study but little difference was recognized between them with respect to the oceanographic conditions The results obtained at Syowa Station were compared with those at Mawson and McMurdo In summer the oceanographic conditions at Syowa were similar to those at Mawson, and in winter the conditions at Syowa resembled those at McMurdo departmental bulletin paper